Hubungan antara Meaning in Life dan Career Anxiety pada Mahasiswa Tingkat Akhir di Kota Bekasi - Amelia Indarti; Erik Saut H. Hutahaean; Ferdy Muzzamil (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to determine the relationship between meaning in life and career anxiety among final-year students in Bekasi City. This study involved 164 respondents who were final-year students, both those domiciled and studying in Bekasi City and those domiciled in Bekasi City and studying in the Greater Jakarta area. The study used a quantitative approach with a non-probability sampling technique through a purposive sampling method. Data collection was carried out using two measuring instruments, namely the meaning in life scale and the career anxiety scale arranged in the form of a Likert scale. Data analysis was carried out with the help of JASP software version 0.19.3.0. A correlation test was used to examine the relationship between the two research variables. The results of the analysis showed a significance value (p > 0.05), which indicated that there was no significant relationship between meaning in life and career anxiety in final-year students. This finding suggests that students' career anxiety levels are not always influenced by their sense of meaning in life.